2014 Seventh International Symposium on Computational Intelligence and Design 2014
DOI: 10.1109/iscid.2014.93
|View full text |Cite
|
Sign up to set email alerts
|

Palm Vein Recognition Based on Multi-algorithm and Score-Level Fusion

Abstract: In order to improve the recognition rate of palm vein recognition algorithm, a recognition algorithm based on SIFT and ORB features extraction and score-level fusion is presented in this paper. Score-level fusion is an information fusion technique, which has six common combination rules. Two dynamic weight combination rules are proposed as a supplement here. The main steps of the proposed algorithm are: First, extract Region of interest (ROI) from the registered palm vein image and the to-be-matched palm vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Our experiments with separate left/right hands matching indicated that reducing the total number of inter class matches causes a significant drop of EER values. Our experiments with bidirectional matching methods on SIFT [9] and RootSIFT [8] resulted in higher EER values than the original research. Especially the EER value difference is significantly high against [9].…”
Section: Experiments and Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Our experiments with separate left/right hands matching indicated that reducing the total number of inter class matches causes a significant drop of EER values. Our experiments with bidirectional matching methods on SIFT [9] and RootSIFT [8] resulted in higher EER values than the original research. Especially the EER value difference is significantly high against [9].…”
Section: Experiments and Resultsmentioning
confidence: 54%
“…To assess the proposed image enhancement method, several palm-vein image recognition systems which use SIFT and RootSIFT features with the CASIA dataset have been implemented. With the SIFT features we applied Euclidian Distance (ED) [6] [8] [9], ED then RANSAC filtering [7].…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations